Robust tunable plasmon induced transparency in coupled-resonance finite array of metasurface nanostructure - Liu, Jie-Tao (Sci Rep, 2021)
Robust and dynamically polarization-controlled tunable plasmon induced transparency (PIT) resonance in designed finite-array nanostructures metasurface is demonstrated, where sharp resonance is guaranteed by design and protected against large geometrical imperfections even for micro-zone sub-array. By employing the explicit analysis of near-field characteristic in the reciprocal-space based on the momentum matching, and the far-field radiation features with point-scattering approach in real-space sparked from Huygens’s principles, the physics of interference resonance for plane-wave optical transmission and reflection of the metasurface is theoretically and thoroughly investigated. The distinctive polarization-selective and Q-tunable PIT shows robust features to performance degradations in traditional PIT system caused by inadvertent fabrication flaws or geometry asymmetry-variations, which paves way for the development of reconfigurable and flexible metasurface and, additionally, opens new avenues in robust and multifunctional controllable nanophotonics device design and applications.